A feeding experiment using captive green sturgeon (Acipenser medirostris Ayres, 1854): Testing non‐invasive methods to assess condition and growth. (1st December 2017) - Corbett, S. C.; Moser, M. L.; Johnson, R. B.; Parker, E. L.
Summary: Non‐invasive methods to determine sturgeon condition are needed for both aquaculture and sturgeon conservation. Such information could help optimize feed choice or holding conditions in aquaculture, and/or allow identification of habitats that are important for sturgeon feeding in the wild. The aim was to determine whether lipid levels (measured by a Distell fish fatmeter) could be used to assess changes in green sturgeon ( Acipenser medirostris ) condition relative to lethal methods (proximate analysis). Thirty non‐reproductive and uniquely marked sturgeon (age 9–11, total length 75.1–114 cm, weight 1.9–7.4 kg) were held at the Conte Anadromous Fish Research Center, Turners Fall, Massachusetts, USA, in Connecticut River water at 14ºC, and under five different rations: 0.1%, 0.25%, 0.5%, 1.0%, and 1.5% body weight/day. Fatmeter readings and conducted proximate composition analysis were taken on muscle tissue of sacrificed animals after 167 days. Five fatmeter measurements were taken at each of three different sites along the dorsal flank above the lateral line. Muscle fat content was determined at the same locations via supercritical fluid extraction (SFE) using carbon dioxide and an ethanol modifier. Fish fed at >0.1% body weight/day gained weight (mean 0.53 ± 0.69–0.74 ± 0.34 kg) and their condition increased by 2%–9% in <6 months. The hepatosomatic index (liver weight/body weight × 100) increased with the ration from 1.12 ± 0.180 (lowest ration) to 1.96 ± 0.357 for fish fed at 0.5% body weight/day. Muscle protein content was positively correlated with the ration and inversely correlated with muscle moisture content. In spite of a wide range of final individual muscle lipid levels determined by proximate analysis (0.5%–3.4%), there was no statistical relationship between the two measures of lipid content, regardless of the position of where they were taken on the sturgeon body. Further refinement of this technology, including species‐specific calibration, is needed if it is to be used on sturgeon either in aquaculture settings or in the wild.